Making absences present: Language policy from below (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
This Special Issue continues the decolonial task of making absences present: of bringing into the frame the linguistic and other knowledges traditionally excluded from educational policy and curricula, and pointing the way to more ethical and equitable forms of knowledge exchange among community members, learners, teachers, researchers, and state actors.